Discussions on the Armenian Genocide in the domestic policy agenda of Germany in 1999-2015 - Tovmasyan, Martin (YSU Journal of International Affairs, 2021)
The article is dedicated to the study of the issue of the recognition of the Armenian Genocide in the German domestic political agenda. The article focuses on the discussions in the German legislature, as it is the most active German political body to discuss the issue of recognizing of Armenian Genocide and condemning genocides. The importance of the topic is further emphasized by the fact that Germany was an ally of Turkey during World War I, so the question arises as to whether Germany does not share the guilt of the crime committed by its ally. We believe that this is one of the possible reasons that has kept Germany from recognizing the Armenian Genocide for a long time. Turkey, on the other hand, is one of Germany’s most important economic and political partners. There are several million Turks living in Germany: Germany cannot ignore these circumstances. However, it is a fact that Germany has honestly acknowledged the atrocities committed by it during World War II, a line that is now reflected in its official policy. Germany also has high-level relations with Armenia, and the issue of recognizing the Armenian Genocide has always been on the agenda of those relations.